Team Phoenix presenting their prototype firefighter uniform - Eisele, John, photographer (Colorado State University. Libraries, 2016)
James Arnold (left) Everlyn Acuna (right).
The 2016 Fairmount Fire Rescue Fire Department Uniform Design was held at the Gifford Building, Colorado State University.
AM375.
SP2016 AM375 Firefighter Uniform Redesign.
Keywords: Fire departments -- Uniforms -- Design -- Awards; Fashion design -- Awards